2017
DOI: 10.1111/cobi.12865
|View full text |Cite
|
Sign up to set email alerts
|

Integrating archaeology and ancient DNA analysis to address invasive species colonization in the Gulf of Alaska

Abstract: The intentional and unintentional movement of plants and animals by humans has transformed ecosystems and landscapes globally. Assessing when and how a species was introduced are central to managing these transformed landscapes, particularly in island environments. In the Gulf of Alaska, there is considerable interest in the history of mammal introductions and rehabilitating Gulf of Alaska island environments by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Given their role in energy metabolism, mitochondrial genes contribute to many adaptive and productive traits, and mitochondrial genome (mtGenome, or mitogenome) variation has been associated with phenotype, including hardiness, disease tolerance and resistance, milk production and fertility (Hiendleder et al 2008; see also MITOMAP.org in human). The definition of these specific diagnostic mutations has also improved phylogenetic information and due to their universal application, mitochondrial DNA markers are used for identification of species in food testing and archaeology (Kitpipit et al 2014;Okuma and Hellberg 2015;Kemp et al 2017;Nikitin et al 2017;West et al 2017). The population and evolutionary biology of mitochondrial DNA (mtDNA) sequences have been extensively studied in many species (Robins et al 2007;Tillmar et al 2013;Wani et al 2014;Sharma et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Given their role in energy metabolism, mitochondrial genes contribute to many adaptive and productive traits, and mitochondrial genome (mtGenome, or mitogenome) variation has been associated with phenotype, including hardiness, disease tolerance and resistance, milk production and fertility (Hiendleder et al 2008; see also MITOMAP.org in human). The definition of these specific diagnostic mutations has also improved phylogenetic information and due to their universal application, mitochondrial DNA markers are used for identification of species in food testing and archaeology (Kitpipit et al 2014;Okuma and Hellberg 2015;Kemp et al 2017;Nikitin et al 2017;West et al 2017). The population and evolutionary biology of mitochondrial DNA (mtDNA) sequences have been extensively studied in many species (Robins et al 2007;Tillmar et al 2013;Wani et al 2014;Sharma et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our study revealed an unexpected and dynamic pattern of extinction and recolonization for a small-bodied carnivore and illustrates that even federally protected or historically pristine ecosystems have experienced more community turnover than previously appreciated. Given that anthropogenic disturbances have driven the turnover of fauna globally, identifying the biogeographic origins of extant species and documenting historical community composition are critical guideposts to establishing restoration baselines 62 and effectively managing both native and non-native species 18 , 19 . Our work also illustrates the importance of continued regional monitoring, the relevancy of historical surveys, and the need for genetic techniques to establish robust and defensible conservation targets.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, extensive conservation programs have been established to protect island biodiversity 14 , 15 and to restore departed island communities 16 , 17 . Historical community composition, though, is not always clear, leading to ambiguous restoration baselines and the potential mismanagement of native and invasive species 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of such associations can lead to potential errors, therefore, failing to achieve valid interpretations, as has been illustrated elsewhere (e.g. Lyman, 2012;Valenzuela & Alcover, 2013a;West et al, 2016). Hence, translocation records need to be connected to tighter radiometric chronologies through direct dating of nonnative animal remains to establish the sequence and timing of introduction events.…”
Section: Introductionmentioning
confidence: 99%